Ball lens as secondary optical element for CPV system. (15th May 2017) - Huang, Qilu; Xu, Lixin
Highlights: A CPV optical system with ball lens as secondary optical element is proposed. Mechanical mounting is used to fix the ball lens on the receiver. This proposed system can minimize the risk of long term reliability. Power generation efficiency of 30.3% and acceptance angle of 0.72° can be obtained. Abstract: Various measures should be taken to optimize the performance, minimize the cost and improve the reliability of CPV concentrator. This paper presents theoretical analysis and experimental verification on a concentrator optical system with geometrical concentration ratio of 625× consisting of a Fresnel lens as primary optical element, a ball lens as secondary optical element and a solar receiver. The solar cell and the ball lens are separated by a small air gap in this proposed CPV system and the ball lens is mounted mechanically on the receiver to enhance the reliability of the CPV system. Test results show that a power generation efficiency of 30.3% and acceptance angle of 0.72° can be obtained for a CPV device with Fresnel lens, ball lens with AR coatings and solar cell with efficiency of 40%.